Características de la Diabetes Mellitus en una red de servicios de primer de nivel de atención. Medellín, 2005-2008 (2011)
ABSTRACT: Because of its severity, frequency and increasing social and economic impact, Diabetes Mellitus (DM) is considered the third priority health problem in the world. Although to date there is no curative treatment, it does have effective measures to reduce its occurrence and limit its complications. Objective: to describe the control program of diabetes in a statewide network of health services in regard to clinical variables, the epidemiology of population served and the control actions, in order to identify strategies for improvement. Methodology: operational research based on secondary data. We reviewed the general conditions of operation of the program based on records of patient care. We studied a random sample of medical records of patients served by the control program of diabetes care units in the network. The results were validated in a meeting with officials of the institution. Results: we detected flaws and points of improvement in the performance of the control program that resulted in specific recommendations for the institutional network. Other failures are due to rules that hinder health system monitoring and control of the DM at the first level. Conclusion: the review of medical records reveals important problems about registration, monitoring and control of diabetics. Other regulatory and contractual provisions of the colombian health system were identified as restrictions that prevent the program to control hyperglycemia and early detection of renal damage. These restrictions could be affecting the programs of control of diabetes in other institutions of the country that are subject to the same rules.